Fintech fundraising challenges in Morocco - ANGUER , Nour-Eddine; BENNIS , Laila (Revue Internationale du Chercheur, 2024)
The fundraising process is a crucial step for fintech companies, aiming to support their growth and innovation. These enterprises are actively engaged in the quest for investments to develop new technologies, expand their market presence, and maintain competitiveness, as they provide numerous opportunities for innovation and transformation of financial services. However, the fundraising process is not without its challenges. Currently, the primary concern for fintech companies lies in seeking funding to expand their operations and introduce innovative services. This document focuses on analyzing the challenges associated with fundraising for fintech in Morocco, hindering the development of this sector at both the national and African levels. Additionally, it examines the solutions envisioned by the government to incubate and support these new players in the market.